Un protocole d'application culturellement pertinent selon les sexes - Association des femmes autochtones du Canada (AFAC) (2011)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; pol4105; premier cycle; périodes historiques; québec; régions géographiques; santé; santé mentale; sciences humaines; sciences sociales; suicide; système colonial; systèmes d'oppressions; thématiques; traumatismes générationnels; travail social; violences

La transphobie en milieu scolaire au Québec : rapport de recherche - Chamberland, Line; Baril, Alexandre; Duchesne, Nathalie; Gilbert, Émond; Julien, Danielle; Otis, Joanne; Ryan, Bill (Université du Québec à Montréal, 2011)
https://www.researchgate.net/publication/284712782_La_transphobie_en_milieu_scolaire_au_Quebec_-_Rapport_de_recherche
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; LGBTQIA2+; amérique du nord; amériques; canada; formations; identités; identités LGBTQIA2+; outils; personnes trans*; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; transphobie; violences; école; étude qualitative

Le bouclier thérapeutique: discours et limites d’un appareil de légitimation - Espineira, Karine (Le sujet dans la cité, 2011)
En 1982, le professeur René Küss plaide à la télévision pour un protocole appelant à distinguer entre « vrais » et « faux » trans’ : de « vrais trans’ » ne causent aucun trouble dans le genre : on leur accorde une aide exceptionnelle (l’opération) par laquelle - hommes devenus femmes ou femmes devenues hommes - ils rentrent dans l’ordre du genre et de l’identité. Telle est l’une des premières expressions de ce que nous proposons d’appeler le « bouclier thérapeutique ». Les trois décennies qui suivent voient s’affronter les affirmations transidentaires et l’idéologie dominante des « traitants ». Appareil de légitimation d’un ordre ancien, le « bouclier thérapeutique » ne serait-il plus aujourd’hui pour ses partisans que le dernier vestige d’une ère marquée par l’effritement d’un deuxième bouclier, juridique celui-ci, garantissant que la libre disposition de l’état civil reste une exception ? Sur ces questions qui interrogent profondément les représentations que nos sociétés se font d’elles-mêmes, peut-être le temps est-il venu d’ouvrir la route tracée par la recherche en sciences sociales et humaines aux nouveaux paradigmes amorcés par les Études de Genre.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; care; cours; discipline; discours; europe; france; inégalités; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; système médical; systèmes d'oppressions; thématiques; transféminisme; violences; violences institutionnelles; violences médicales

The Intersex Enchiridion: Naming and Knowledge - Holmes, Morgan (Somatechnics, 2011)
The 2006 Lawson Wilkins Pediatric Endocrinology Society (LWPES) consensus to alter clinical language from ‘intersex’ to Disorders of Sex Development (DSD) has not met its stated objective of destigmatizing the ‘intersex’ label. Rather, DSD works to paper over a problematic understanding of morphological variation as disease. This article interrogates the development of DSD terminology in the clinical context of treating intersex and argues that ‘DSD’ reinstitutionalises clinical power to delineate and silence those marked by the diagnosis; that this silencing is precisely the point of the new terminology; and that it is against that retrenchant impulse that we must protect the viability of ‘intersex’ by continuing its critical deployment. This paper is based on an application of embodiment studies models of critique, combined with an orientation grounded in queer theory to critically interrogate the development of both DSD language and of the ‘new’ guidelines for clinical use, and of the Handbook for Parents that were developed out of the 2006 LWPES meetings. Some of my critique is based on work done over an 18-year period with adults who created the contemporary intersex movement, and on my previous research (in particular: Holmes 2002, 2008, 2010). The point of the argument is not to determine which diagnostic language is superior, but to retain the hard-won right to secure for ourselves the ability to operate socially without the stamp of ‘disorder’ or ‘disease’ strictly delineating what counts as ‘truth’ with regard to embodiment. In this sense, the argument applies to and is drawn out of a larger disability scholarship and activism framework that refuses to permit medicine the final voice in defining our bodies and our selves. The title refers to an older handbook, the enchiridion as a gesture toward the need to retain fundamental knowledge of self that intersexed persons can trace back to a more flexible understanding of embodied differences than the language of disorder asserts in the new Handbook for Parents.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; identité; intersexuation; militance; personnes intersexes; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; violences; violences médicales; états-unis

Honor killings in the Middle East and North Africa: a systematic review of the literature - Kulczycki, Andrzej; Windle, Sarah (Violence against women, 2011)
A systematic review of the research literature on honor killings in the Middle East and North Africa (MENA) indicates a paucity of studies relative to the presumed magnitude of the problem. Forty articles were reviewed and critically appraised, of which only 9 contained primary data and 11 presented original secondary analyses. Despite a recent increase in published studies, persistent methodological limitations restrict the generalizability of findings. Most studies focus on legal aspects, determinants, and characteristics of victims and perpetrators. Victims are mostly young females murdered by their male kin. Unambiguous evidence of a decline in tolerance of honor killings remains elusive.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; cours; droits des femmes*; féminisme islamique; maghreb; moyen-orient; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sex2283; sexisme; systèmes d'oppressions; thématiques; violences

Je suis encore sauvage ! ! ! - Vollant, Mali-Jane (Recherches amérindiennes au Québec, 2011)
Texte personnel décrivant les relations d'une famille autochtone à ma terre et leur combat contre un projet d'exploitation minière sur leur territoire.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; capitalisme; cours; environnement; exploitation minière; histoire et politique; justice sociale; militance; pol4105; premier cycle; périodes historiques; québec; régions géographiques; système colonial; systèmes d'oppressions; territoire; thématiques; uashat–mani-utenam; violences; écologie